A Putative Role for Ubiquitin-Proteasome Signaling in Estrogenic Memory Regulation - Beamish, Sarah B.; Frick, Karyn M. (Frontiers in Behavioral Neuroscience, 2022)
Sex steroid hormones such as 17β-estradiol (E2) are critical neuromodulators of hippocampal synaptic plasticity and hippocampus-dependent memory in both males and females. However, the mechanisms through which E2 regulates memory formation in both sexes remain unclear. Research to date suggests that E2 regulates hippocampus-dependent memory by activating numerous cell-signaling cascades to promote the synthesis of proteins that support structural changes at hippocampal synapses. However, this work has largely overlooked the equally important contributions of protein degradation mediated by the ubiquitin proteasome system (UPS) in remodeling the synapse. Despite being critically implicated in synaptic plasticity and successful formation of long-term memories, it remains unclear whether protein degradation mediated by the UPS is necessary for E2 to exert its beneficial effects on hippocampal plasticity and memory formation. The present article provides an overview of the receptor and signaling mechanisms so far identified as critical for regulating hippocampal E2 and UPS function in males and females, with a particular emphasis on the ways in which these mechanisms overlap to support structural integrity and protein composition of hippocampal synapses. We argue that the high degree of correspondence between E2 and UPS activity warrants additional study to examine the contributions of ubiquitin-mediated protein degradation in regulating effects of sex steroid hormones on cognition.